Expert Consensus on Bilateral Inferior Petrosal Sinus Sampling in the Diagnosis of Cushing′s Syndrome (2023) - Chinese Medical Association Rare Diseases Branch, Hypothalamic and Pituitary Disease Group of China Alliance of Rare Diseases (CARD); Innovation Center of Pituitary Diseases, Peking Union Medical College Hospital (罕见病研究, 2023)
Cushing′s syndrome(CS)is a clinical syndrome caused by a variety of causes, with main manifestations exhibited by central obesity, purple skin striae, hypertension, and diabetes. In patients with adrenocorticotropic hormone(ACTH)-dependent CS, the result of bilateral inferior petrosal sinus sampling(BIPSS)is the gold standard for determining the source of ACTH in the absence of routine imaging findings.However, the indications, contraindications, operating procedures, precautions and outcome judgments of BIPSS differ from one medical center to another, and there are currently no international and domestic clinical guidelines and expert consensus on BIPSS. In order to further improve the operation specifications of BIPSS in the diagnosis process of difficult CS, the Hypothalamic and Pituitary Disease Group of the China Alliance for Rare Diseases and the Innovation Center of Pituitary Diseases of Peking Union Medical College Hospital organized experts in endocrinology, interventional radiology, neurosurgery and laboratory in China to formulate this consensus. This consensus aims to provide standardized methodological guidance for the use of BIPSS in the differential diagnostic process of CS in clinical practice.